Physical geology : - Monroe, James S (West, 1995)
How does the planet work and why is this important to know? In PHYSICAL GEOLOGY: EXPLORING THE EARTH doesn't just explain physical geology and its processes; it places that knowledge within the context of human experience by consistently emphasizing relevance, resources, and the environment. The authors consistently demonstrate how geology relates to the human experience. Explore your reaction to particular situations through "What would you do?" questions throughout the text. "Geology in Your Life" sections address today'sconcerns, especially in the areas of environment and energy.